Modern approaches to the rehabilitation of people with chronic back pain of various genesis - Tereshchuk, Ольга; Dorofieieva , Олена; Yarymbash , Ксенія (Psychosomatic Medicine and General Practice, 2024)
This text is the abstract of the report of the Scientific and Practical Conference "War Trauma. Multimodal Approach in Inpatient Treatment", June 22 - 22, 2024, online and offline - Kyiv, 21 Akademika Zabolotnoho St., Clinical Hospital "Feofania" of the State Medical University.